Training on Making Hand Sanitizers Made from Local Plants to Prevent the Spread of Covid-19 (Case Study in Kambu District Kendari City) - Satya Darmayani; Bestfy Anitasari; Sutiharni Sutiharni; Resy Nirawati; Marni Br Karo (Carmin: Journal of Community Service, 2023)
This activity is expected to be a solution to prevent the spread of Corona Virus Disease (Covid-19), which is becoming a global pandemic. This effort is expected to provide additional knowledge to the community about how to make, function, and component, the practice of making and using hand sanitizers made from natural non-alcoholic, and non-toxic ingredients from local plants that are easy to obtain. This activity was carried out in September 2022. Counseling begins with the presentation of material through interactive presentations and discussions with the target subject. Then the counseling continued with the practice of making and using hand sanitizers made from local plants: lime, mint leaves, and aloe vera gel. The activity's success can be said to be successful because it is seen from the participation of the target audience, namely 75% of the targeted minimum of 60%, and the implementation of all community service procedures thoroughly and adequately by the implementing committee of community service activities.